Constructing a Shared Vision: Otto Koenigsberger and Tata & Sons - Rachel Lee (ABE Journal)
Although Otto Koenigsberger (1908–1999) began working in India eight years before the country won independence, he was not part of the British Raj’s colonial enterprise. As Government Architect of the semi-autonomous Princely Mysore State and later as Federal Director of Housing, as well as through his private architecture and planning practice, Koenigsberger worked on building the independent Indian nation from within. In this paper, the author will argue that the high profile private commissions for Tata & Sons—a privately owned and hugely influential industrial corporation committed to nationalism and philanthropy—both forwarded Koenigsberger’s career and directly contributed to building the infrastructure of independent India.As the basis for their sustained and successful collaboration, the author will demonstrate that Koenigsberger’s notion of a locally rooted, research-based “scientific architecture,” overlapped with the Tata Group’s philosophy of advancing India through science and technology. Moreover she will shed light on the networks of India’s cultural elite, illustrating that connections in the international realm of physics were responsible for the initial contact between the refugee architect and the industrial concern. While showing that his work with the Tatas enabled Koenigsberger to realise his architectural and planning goals more fully than his work as a government architect, the author proposes that the vision shared by Koenigsberger and the Tatas, and the projects they undertook, played a role in the dissolution of the British empire in India.